Canine Snake-Eye Myelopathy: Clinical, Magnetic Resonance Imaging, and Pathologic Findings in Four Cases - Rossmeisl, John H.; Cecere, Thomas E.; Kortz, Gregg D.; Geiger, David A.; Shinn, Richard L.; Hinckley, Jonathan; Caudell, David L.; Stahle, Jessica A. (Frontiers in Veterinary Science, 2019)
Intramedullary signal change (ISC) is a non-specific finding that is frequently observed on magnetic resonance imaging (MRI) examinations of the canine spinal cord. ISC can represent a variety of primary pathological processes such as neoplasms or myelitides or secondary changes such as edema, cysts, gliosis, or myelomalacia. An unusual phenotype of ISC is the “snake-eye” myelopathy (SEM), which refers to bilaterally symmetric T2 hyperintensities preferentially affecting the ventral horn gray matter on transverse MR images, which resemble a pair of snake's eyes. The pathophysiology of SEM is poorly understood in humans, and this imaging finding may be associated with cervical spondylotic myelopathy, spinal cord ischemia, ossification of the posterior longitudinal ligament, amyotrophic lateral sclerosis, and Hirayama disease. Here we describe 4 dogs with cervical MRI examinations consistent with an SEM-like phenotype. All dogs initially presented with a central cord syndrome or tetraparesis referable to a C6-T2 neuroanatomic localization, which was attributed to disc-associated spinal cord compression in 3 cases, while one dog had the SEM-like phenotype with no identifiable etiology. Once the SEM-like phenotype was present on MRI examinations, dogs demonstrated insidious clinical deterioration despite therapeutic interventions. Deterioration was characterized by lower motor neuron weakness and neurogenic muscle atrophy progressing to paralysis in the thoracic limbs, while neurological functions caudal to the level of the SEM-like lesion remained largely preserved for months to years thereafter. Neuropathological features of the SEM-like phenotype include multisegmental cavitations and poliomyelomalacia of laminae VI-IX of the caudal cervical spinal cord, although the lesion evolved into pan-necrosis of gray matter with extension into the adjacent white matter in one case with an 8-year history of progressive disease. Although the pathophysiology of SEM remains unknown, the topographical distribution and appearance of lesions is suggestive of a vascular disorder. As the SEM-like phenotype was uniformly characterized by longitudinally and circumferentially extensive neuronal necrosis, results of this small case series indicate that dogs with clinical signs of central cord syndrome and the SEM-like phenotype involving the cervicothoracic intumescence on MR examinations have a poor prognosis for the preservation or recovery of thoracic limb motor function.